Mild profile improvement of immune biomarkers in HIV/HCV-coinfected patients who removed hepatitis C after HCV treatment: A prospective study. Issue 1 (January 2020) - Garcia-Broncano, Pilar; Medrano, Luz Maria; Berenguer, Juan; Brochado-Kith, Oscar; González-García, Juan; Jiménez-Sousa, Ma Ángeles; Quereda, Carmen; Sanz, José; Téllez, María Jesús; Díaz, Laura; JIménez, José Luis; Resino, Salvador; et al.
Highlights: We evaluated the changes in the medium-term of a large number of biomarkers in HIV/HCV-patients who achieved SVR. HIV/HCV-patients showed a slight improvement in the overall profile of immune biomarkers after achieving SVR with peg-IFN-α/ribavirin. It would be necessary to evaluate whether these biomarkers approximate levels in those who never had chronic hepatitis C. Abstract : Objective: There are a lack of consistency among articles in regards to the evolution of peripheral immune biomarkers after HCV therapy. We aimed to detect the most relevant changes in peripheral immune biomarkers among HIV/HCV-coinfected patients who achieved sustained virologic response (SVR) following peg-IFN-α/ribavirin therapy and to evaluate its normalization with respect to an HIV-monoinfected control group. Methods: We performed a prospective cohort study in 99 HIV/HCV-coinfected patients with samples at baseline (HIV/HCV-b-group) and at week 24 after SVR (HIV/HCV-f-group). We also used a control group of 39 HIV-monoinfected patients (HIV-group) negative for HCV and HBV infections, and who had undetectable HIV viral load and CD4 + >500 cells/mm 3 . Peripheral T cell subsets were assessed by flow cytometry and plasma biomarkers by immunoassays. Results: HIV/HCV-coinfected patients had higher values of in IL-10, IL-4, IP-10, IL-8, IL-1β, IL-18, IL-6, IFN-γ, IL-12p70, TNF-α, sVCAM-1, sICAM-1, and sTNFR-1 than HIV control subjects, both at the beginning and at the end of follow-up. Moreover, three biomarkers (CD4 + CD38 +, telomere length, and IL-1RA) were normalized in relation to the control group at the end of follow-up (the HIV/HCV-b group had higher values and the HIV/HCV-f group had similar values as the HIV-group). Additionally, LPS, IL-2, and IL-17A levels were higher in the HIV/HCV-f group than the HIV-group (24 weeks after SVR). During the follow-up, HIV/HCV-coinfected patients had a significant decrease by the end of follow-up in CD8 + CD45RA − CD28 +, CD4 + CD38 +, CD4 + CD25 + CD127 −/low, CD4 + CD25 + CD127 −/low CD45RA −, FABP2, LBP, IP-10, sVCAM1. Only CD4 + CD38 + was normalized. Conclusion: HIV/HCV-patients showed a slight improvement in the overall profile of immune biomarkers after achieving SVR.